2001
DOI: 10.1038/84781
|View full text |Cite
|
Sign up to set email alerts
|

The putative forkhead transcription factor FOXL2 is mutated in blepharophimosis/ptosis/epicanthus inversus syndrome

Abstract: In type I blepharophimosis/ptosis/epicanthus inversus syndrome (BPES), eyelid abnormalities are associated with ovarian failure. Type II BPES shows only the eyelid defects, but both types map to chromosome 3q23. We have positionally cloned a novel, putative winged helix/forkhead transcription factor gene, FOXL2, that is mutated to produce truncated proteins in type I families and larger proteins in type II. Consistent with an involvement in those tissues, FOXL2 is selectively expressed in the mesenchyme of dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
696
3
21

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 880 publications
(726 citation statements)
references
References 45 publications
6
696
3
21
Order By: Relevance
“…It was generally believed that mouse eyelid formation starts at E13 (Crisponi et al, 2001;Findlater et Juriloff et al, 2000). This is perhaps because the protruding ridges become apparent during this stage of development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was generally believed that mouse eyelid formation starts at E13 (Crisponi et al, 2001;Findlater et Juriloff et al, 2000). This is perhaps because the protruding ridges become apparent during this stage of development.…”
Section: Discussionmentioning
confidence: 99%
“…It was recently reported that mutations leading to truncation of FOXL2, a putative forkhead transcription factor, results in an autosomal dominant disorder, blepharophimosis/ptosis/epicanthus inversus syndrome (BPES). BPES patients exhibit eyelid abnormalities characterized by small palpebral fissures, drooping eyelids, and a tiny skin fold running inward and upward from the lower lid (Crisponi et al, 2001). As no homozygous patients have been reported, it is impossible to predict the appearance of homozygous eyelids.…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in FOXL2 cause blepharophimosis, ptosis, epicanthus inversus syndrome (OMIM #110100), and blepharophimosis, ptosis, epicanthus inversus syndrome type I is accompanied by premature ovarian failure of the affected female (Crisponi et al, 2001). FOXL2 is mainly expressed in undifferentiated granulosa cells, and blockage of ovarian follicle development because of the failure of granulosa cell differentiation was observed in FoxL2 lacZ homozygous mutant mice (Pisarska et al, 2004;Uda et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, forkhead domain genes were found to be affected in tumorigenesis and in several human congenital syndromes (Li and Vogt, 1993;Barr, 1997;Chatila et al, 2000;Crisponi et al, 2001;Karkkainen et al, 2001;Lai et al, 2001;Wildin et al, 2001).…”
Section: Introductionmentioning
confidence: 99%